Does intrauterine exposure to hypercholesterolemia adversely affect familial hypercholesterolemia phenotype?. Issue 4 (August 2016) - Bogsrud, Martin P.; Ulven, Stine M.; Holven, Kirsten B.
Abstract : Purpose of review: There is currently limited information as to whether maternally or paternally inherited familial hypercholesterolemia confers different phenotype risk to offspring. Knowledge about the differences in risk conferred by inheritance could be important with respect to follow-up and more individually targeted treatment of subjects with familial hypercholesterolemia. Recent findings: Few studies have, with inconsistent results so far, investigated the significance of familial hypercholesterolemia inheritance on cardiovascular risk markers in offspring. Maternal inheritance of familial hypercholesterolemia includes hypercholesterolemic in-utero conditions for the offspring. How this may influence later risk is briefly discussed in the article. Summary: Current data suggest that the dominating factor of the familial hypercholesterolemia (FH) phenotype is the mutation and not the inheritance, however, maternal inheritance of FH has been reported to adversely affect FH phenotype in terms of increased mortality. More knowledge about how intrauterine hypercholesterolemia during pregnancy influences epigenetic modifications and later cardiovascular disease risk in offspring is needed and this may open up new avenues of treatment of pregnant women with familial hypercholesterolemia.